REFORMASI BIROKRASI DALAM PELAYANAN PUBLIK PADA KANTOR AGRARIA DAN TATA RUANG / BADAN PERTANAHAN NASIONAL (ATR / BPN ) KABUPATEN MAROS - Andi Patta Yusuf; Muh. Akmal Ibrahim; Syahribulan Syahribulan (Universitas Musamus, Merauke, Papua, 2019)
Bureaucratic Reform in Public Service has been known in this case the land service is still convoluted and the process spent a long time indicating not yet in accordance with procedure established by BPN. This study aims to examine the implementation of bureaucracy reform in public service at the Office Agraria and Tata Ruang/Badan Pertanahan Nasional (ATR/BPN) Maros Regency based on Bureaucratic Reform Strategy. This research uses qualitative approach. Sources of data used are primary and secondary data. The result of the research shows that the implementation of bureaucratic reform in public service at the Office Agraria and Tata Ruang/Badan Pertanahan Nasional (ATR/BPN) Maros Regency can not reach the public service in the field of land according to the procedure as determined by the head of national land agency about service standard and land arrangements in land certificate management, this is caused by many priority programs given directly from the center in addition to the routine services faced to make the workload over due to the availability of human resources in this case the employee of the meter there are only seven people while the land who want to be measured that the number of fields is quite large approximately + 9354 fields every year and in the implementation of reforms in areas that can not be done that is recruitment of employees. Recruitment of these employees is the authority of the center so that it can hinder land services to the community.